Diagnostic delay in Crohn's disease is associated with increased rate of abdominal surgery: A retrospective study in Chinese patients. Issue 7 (July 2015) - Li, Yuan; Ren, Jianan; Wang, Gefei; Gu, Guosheng; Wu, Xiuwen; Ren, Huajian; Hong, Zhiwu; Hu, Dong; Wu, Qin; Li, Guanwei; Liu, Song; Anjum, Nadeem; et al.
Abstract Background Diagnostic delay of Crohn's disease presents a challenge, and may increase the abdominal surgery rate. There have been no reports regarding diagnostic delay in Chinese patients. Aims We aimed to evaluate the impact of diagnostic delay on outcomes of Chinese Crohn's disease patients, and identify potential risk factors for the delay. Methods Altogether, 343 Crohn's disease patients from our hospital were retrospectively included. We assessed the effects of diagnostic delay on the outcomes, and identified the underlying risk factors. Results Diagnostic interval was defined as the interval between the first symptoms and the diagnosis of Crohn's disease. Diagnostic delay was defined according to the time interval in which the 76th to 100th percentiles of patients were diagnosed. The rates of subsequent surgery for diagnostic-delay and non-diagnostic-delay patients were 84.7% and 62.4%, respectively (odds ratio = 1.108, P < 0.0001). We found statistical differences between the two groups regarding age >40 years at diagnosis (35.3% versus 18.2%, P = 0.004), basic educational level (48.2% versus 30.6%, P = 0.005), and no family history of Crohn's disease (0 versus 1.6%, P = 0.045). Conclusions Diagnostic delay of Crohn's disease was significantly associated with increased rates of intestinal surgery. Risk factors for diagnostic delay were age >40 years at diagnosis, basic educational level, and no family history of Crohn's disease.